Impact of Marital Status, Education, and Family Size on Parental Behaviors Toward Early Childhood Caries in Romania - Abel Emanuel Moca; Ioan Andrei Țig; Jessica Olivia Cherecheș; Rahela Tabita Moca; Raluca Iurcov (Dentistry Journal)
Background and Objectives: This study aimed to examine the influence of socio-demographic factors (marital status, number of children, and education level) on the knowledge, attitudes, and practices (KAP) concerning Early Childhood Caries (ECC) prevention among parents in Bihor, Romania. This research seeks to address the lack of regional data on the influence of socio-demographic factors, such as marital status, number of children, and education level, on parental knowledge, attitudes, and practices regarding ECC prevention. These insights are essential for developing targeted public health interventions in Romania. Materials and Methods: Conducted from March to September 2024, this cross-sectional study utilized a KAP questionnaire distributed online to parents of children under six. The survey was adapted to local contexts and included sections on demographic data and ECC-specific knowledge, attitudes, and practices. Statistical analyses, including Chi-square tests, were performed to evaluate the relationship between socio-demographic factors and KAP outcomes, ensuring robust data interpretation under ethical standards set by the Declaration of Helsinki. Results: Of the 798 respondents who accessed the questionnaire, 419 completed it, resulting in a completion rate of 52.5%. The participants had a mean age of 33.8 years. In terms of gender distribution, 348 (83.1%) were female and 71 (16.9%) were male. Higher educational levels were strongly correlated with better ECC knowledge and preventive practices; parents with university degrees demonstrated significantly better understanding and engagement in ECC prevention (p < 0.05). Married parents participated more actively in ECC prevention than unmarried ones, with 61.1% adhering to recommended practices compared to significantly lower rates among unmarried parents (p = 0.020). While this difference was statistically significant, the lower representation of unmarried parents in the sample should be considered when interpreting this finding. Families with fewer children showed more effective ECC preventive practices (p = 0.001). Conclusions: The study suggests that higher education and smaller family sizes are associated with better ECC prevention behaviors, emphasizing the need for targeted public health interventions. These could include parental education campaigns on ECC prevention, community-based oral health workshops, subsidized fluoride programs, and increased accessibility to pediatric dental services for underprivileged families.